1994
DOI: 10.1088/0965-0393/2/4/001
|View full text |Cite
|
Sign up to set email alerts
|

Cellular automaton simulations of cement hydration and microstructure development

Abstract: Cellular automaton algorithms, which operate on a starting digital image of a water-cement suspension, are described. The algorithms simulate the microstructure development process due to hydration reactions that occurs between cement and water. This paper describes the evolution of the cement model from a simple model, which treated the cement particles as single-phase materials, with a greatly simplified hydration chemistry, into a model which has many more chemical species and includes numerous reactions wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(32 citation statements)
references
References 24 publications
1
29
0
2
Order By: Relevance
“…The lattice structure is the computational 'back-bone', whereas in Vonk's model, for example, or the 'numerical concrete' model by Roelfstra et al (1985) the two-or three-dimensional finite elements have to be fitted to the complex material structure, which is particularly tedious in three dimensions. Independent generation of lattice and particle structure also opens the way to Examples of computer generated material structure intended to mimic the structure of concrete at the meso-level: (a) Burt and Dougill (1977), (b) Vonk et al (1991) and (c) Schlangen and Van Mier (1992) use real aggregate shapes, as was demonstrated by Schlangen and Garboczi (1997), in a way similar to the generation of computational cement hydration models pioneered at NIST by Bentz et al (1994).…”
Section: Simple Lattice Approachmentioning
confidence: 97%
See 3 more Smart Citations
“…The lattice structure is the computational 'back-bone', whereas in Vonk's model, for example, or the 'numerical concrete' model by Roelfstra et al (1985) the two-or three-dimensional finite elements have to be fitted to the complex material structure, which is particularly tedious in three dimensions. Independent generation of lattice and particle structure also opens the way to Examples of computer generated material structure intended to mimic the structure of concrete at the meso-level: (a) Burt and Dougill (1977), (b) Vonk et al (1991) and (c) Schlangen and Van Mier (1992) use real aggregate shapes, as was demonstrated by Schlangen and Garboczi (1997), in a way similar to the generation of computational cement hydration models pioneered at NIST by Bentz et al (1994).…”
Section: Simple Lattice Approachmentioning
confidence: 97%
“…The reaction with water is called hydration and proceeds only controlled when gypsum is included. The emerging structure is rather complicated, and for a good overview of the matter, the reader is referred to the various publications dealing with cement hydration, for example Bentz et al (1994) and Bentz (1997) and more recently Pignat et al (2005). The hydration starts at places where cement comes into contact with water, and results in a complicated microstructure, like the one visible in Fig.…”
Section: What Happens At Micro-scales and Beyond?mentioning
confidence: 99%
See 2 more Smart Citations
“…After execution of each cycle of the model, digital image processing techniques may be employed to determine the new phase volume fractions, etc. In addition to the present model for cement hydration [5,20], CA-type models have been developed for sintering [21], dendritic growth [22], and the carbonation of cement [23].…”
Section: Cellular Automatamentioning
confidence: 99%